WHICH ONE IS BETTER BETWEEN PAPER-BASED OR COMPUTER-BASED TOEFL?: TEST TAKERS’ PERSPERCTIVES - Faridatul Istighfaroh; Junaidi Mistar; Mutmainnah Mustofa; Sonny Elfiyanto (EDUTECH, 2023)
Due to the lack of current study numbers discussing English proficiency tests such as TOEFL, this study aims to investigate the test takers’ point of view on the TOEFL ITP test, mainly paper based-test and computer-based TOEFL, the similar TOEFL ITP test but employing computer screen as media. The latest study about those two assessments is necessary since both kinds of TOEFL media are massively implemented, particularly backward and after the pandemic Covid19. A survey methodology is employed in this study by spreading questionnaires. The scores gained from those two disparate TOEFL tests are described statistically. The gathered data were then analyzed using descriptive statistics and factor analysis to outline the perspectives of the test-takers on TOEFL PBT and CBT. Fifty-two participants from various education background levels, ages and genders partaking in this study. As a result, this study reveals that the implementing a computer screen for TOEFL obtained more positive percentages than paper-based TOEFL tests. Further discussion concerning prior study and implications are presented